Performance of buri palm (corypha utan) reinforced epoxy composite : effect of alkali treatment - Zalinawati, Muhamad (2021)
The development of polymer composites using natural fiber reinforced polymer has grown in recent years due to increase in environmental awareness. Natural fibers are much cheaper than synthetic fibers and can be used as a subtitute in applications, where the cost concern outweighs strength requirements. Due to the low cost in comparison to synthetic fibers, the buri (corypha utan) fiber reinforced composites have great potential to be used in engineering applications. The aim of this study was to analyse density, Fourier transform spectroscopy (FTIR), and physical and mechanical properties of the single- strand buri palm fiber in different conditions of surface modification, one with 5 wt.% and the other with 10 wt.% sodium hydroxide (NaOH) for 1 and 24 h immersion. This study was to fabricate the buri palm fiber reinforced epoxy composite and evaluate the effects of fiber treatment on water absorption, tensile properties and flexural properties. The density of buri palm fiber showed that a higher NaOH solution concentration and immersion period leads to lower density. The best treatments of single-strand treated with 5 wt.% 24 h immersion showed the highest tensile strength of 159.16 MPa. It was used to fabricate the composite of four-layers and five-layer stacking sequence composite made by using hand lay-up technique and hydraulic press. The water absorption experiment was conducted by immersing the specimen in distilled water at room temperature until it reached the saturated moisture absorption. The percentage of moisture uptake was reduced to 69% and 95% in treated four-layer and five-layer sequences. It is observed that the thickness swelling of the composite increased with the increase of sequence layering, while the thickness swelling decreased with the treated fiber. The results for dry composites show that the five-layer treated gave the highest tensile strength and flexural of 33.51 MPa and 56.72 MPa. Finally, morphology examinations were carried out to analyse the fracture behavior and fiber failure on the tensile test specimen by using Scanning electron microscopy (SEM) and microscope analysis. In conclusion, it would appear that the mechanical properties increased as increase of sequence layering treated fiber composite. Alkali treatment affected the properties of buri palm fiber which improved the interfacial bonding between the fiber and epoxy matrix for better tensile properties and reduced water absorption.